High-coercivity FePt nanoparticle assemblies embedded in oxide-matrix by atomic layer deposition - Kong, J.-Z. (2015)
Self-assembled face-centered cubic FePt nanoparticles were embedded into the oxide capping layer using the atomic layer deposition technology. The effect of the oxide-matrix layer on the structure, mono-dispersibility, and magnetic properties of the FePt/oxide composite thin films was investigated. Experimental results suggest that the protection of the oxide-matrix capping layer can effectively inhibit the grain growth and particle aggregation, and preserve the ordered domains of the FePt nanoparticles during the L10 ordering transition through annealing. The combination of the atomic layer deposition capping layer and self-assembled FePt nanoparticles provides a new potential approach to fabricate the ultrahigh-density magnetic recording media.